Reporte sobre el diseño del programa de investigaciones arqueológicas en el Monumento Nacional Guayabo de Turrialba - Alarcón Zamora, Gerardo Miguel (2015)
Since 2010, actions towards establishing a program of archaeological investigation at the National Monument Guayabo de Turrialba have been set in motion by the School of Anthropology of the University of Costa Rica. Specific activities performed by the program include contacting specialists in restoration of archaeological sites and effecting investigative projects and teaching programs, in collaboration with the Schools of Topographic and Civil Engineering, also from the University of Costa Rica.